Pyruvate Kinase Is Required for Sex Pheromone Biosynthesis in Helicoverpa armigera - Yao, Shuangyan; Zhang, Yunhui; Chang, Yanpeng; Li, Xiang; Zhao, Wenli; An, Shiheng (Frontiers in Physiology, 2021)
Pyruvate kinase (PYK) is a speed-limited enzyme of glycolysis that catalyzes the formation of pyruvate and plays an important role in acetyl-CoA synthesis. The acetyl-CoA is the precursor of sex pheromone biosynthesis in Helicoverpa armigera. However, the role of PYK in sex pheromone biosynthesis remains elusive. Here, PYK in H. armigera (HaPYK) was found to be highly expressed in the pheromone glands (PGs). The developmental expression profile of HaPYK was consistent with the fluctuation of sex pheromone release. Function analysis revealed that the knockdown of HaPYK led to a decrease in levels of pyruvic acid and acetyl-CoA in PGs, which in turn caused to a significant decrease in cis-11-hexadecenal (Z11-16: Ald) production, female capability to attract males and mating frequency. Further study demonstrated that sugar feeding (5% sugar) increased the transcription and enzyme activity of HaPYK, ultimately facilitating to sex pheromone biosynthesis. Moreover, pheromone biosynthesis activating neuropeptide (PBAN) up-regulated HaPYK activity through protein kinase C (PKC), as shown by PKC-specific inhibitor analysis. Altogether, our results revealed that PBAN activated HaPYK by Ca2+/PKC, thereby regulating the synthesis of pyruvate and subsequent acetyl-CoA, ensuring the supply of sex pheromone precursor, and finally facilitating to sex pheromone biosynthesis and mating behavior.